Unleashing analytical mastery: elevating HOTS with hybrid project-based learning in academic writing courses - Rochmahwati, Pryla; Yuliasri, Issy; Sukarno, Sukarno; Pratama, Hendi (Institute of Advanced Engineering and Science, 2024)
This groundbreaking study addresses a significant research gap in modern pedagogy by examining the revolutionary effects of hybrid project-based learning (HPBL) on high-order thinking skills (HOTS) in English as a foreign language (EFL) writing instruction. By employing a quasi-experimental design and incorporating the participation of 85 students as a population, this study addresses two crucial inquiries: i) the degree to which HPBL impacts the overall writing abilities of EFL students enrolled in an academic writing course and ii) how HPBL enhances the analytical capabilities of the students. The argumentative writing test was employed as a research instrument. The research demonstrates a significant writing and analytical mastery enhancement through rigorous paired sample testing and validation. This research not only makes substantial contributions to the ongoing scholarly discourse but also underscores the critical significance of further exploring the dynamic attributes of HPBL, thus further establishing its position as an indispensable element of modern language instructions.